The effect of incentives, work passion and job satisfaction on vocational secondary school (SMK) teacher work achievement in the City Of Medan, Indonesia - Djatmiko Noviantoro (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2018)
Purpose: This study aims to empirically investigate the direct effect of incentives on job satisfaction, and the extent of direct effect of work passion on job satisfaction, the extent of direct effect job satisfaction on teachers' achievement, the extent of direct effect of incentives on teachers' achievement, and the extent of direct effect of work passion on teachers' achievement, and the effect of incentives on teachers' achievement through job satisfaction, as well as the extent of the effect of work passion on teachers' achievement through job satisfaction. Design/methodology/approach: This study involved a sample of 183 SMK teachers across the City of Medan. The data were analyzed using "Path Analysis" of IBM SPSS 21.0. [...] Research limitations/implications: Despite the variable of incentives have a nonsignificant direct effect on work achievement and work passion and job satisfaction have a significant effect on improvement of work achievement, this variable, however, must be well implemented and improved on a continuous basis in order to achieve best work achievement so as to maximally achieve the pre-defined goals or objectives. Originality/value: Researches can add several more variables, both of exogenous variables and endogenous variables for the purpose of improving and expanding the results of this research, so that the expected findings may bring more benefits for the development and advancement of education world especially in the City of Medan. In addition, the municipal Government of Medan can also take strategic steps that may help improve the quality of education in the City of Medan in general and in particular.
Keywords: I20; I29; N3; 330; Incentives; Work Passion; Job; Satisfaction; Achievement